The fate of Eichhornia azurea (Sw.) Kunth. detritus within a tropical reservoir - Santino,Marcela Bianchessi da Cunha (2010)
AIM: This study is aimed at comparing the kinetics of decomposition of Eichhornia azurea and discussing the fate of its detritus; METHODS: The samples of aquatic macrophytes and water were collected in the Piraju Reservoir (São Paulo State, Brazil). The plant material was oven-dried and triturated and for each experimental condition (aerobic and anaerobic), 72 mineralization chambers were prepared with plant fragments and reservoir water. On sampling days the particulate and dissolved organic matter were quantified (on carbon basis POC and DOC, respectively); RESULTS: The decomposition of E. azurea is more efficient under aerobic conditions, being 2.2 times faster than for the anaerobic process, according to the amount of mineralized carbon. For the decay of leaves, stems and roots of E. azurea the aerobic processes were 1.22-fold faster. It is assumed that the fractions responsible for the high oxygen consumption have reduced periods of half-time, and therefore do not accumulate in the ecosystems. Owing to the biomass of E. azurea in the Piraju Reservoir, the aerobic decay of E. azurea can promote moderate depletion in the dissolved oxygen budget. With the rate of the mineralization of refractory materials (Ξ half-time varying from 385 to 462 days), the fibrous debris of this plant, i.e. refractory fractions, associated with the appropriate conditions of pH and oxi-reduction potential, can contribute to the gas production and storage of particulate organic matter in sediments.